Nano montmorillonite powder activated rubber polyurethane concrete as well as preparation method and application thereof

By using nanomontolite powder and activated rubber composite modification technology in polyurethane concrete, the problem of prone to cracks, delamination and other diseases on the steel bridge deck is solved, and higher toughness, fatigue resistance and high Low temperature tolerance provides a more reliable and long-lasting steel bridge deck paving solution.

CN119461951APending Publication Date: 2025-02-18SHANDONG TRAFFIC PLANNING DESIGN INST
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411628260.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing polyurethane concrete is prone to cracks, delamination and other diseases on the steel bridge deck, and its durability is not ideal, making it difficult to meet the strict environmental requirements of steel bridge deck paving.

Method used

The modified polyurethane concrete of nanomontorite powder and activated rubber is used to improve the toughness, fatigue resistance and high and low temperature resistance of the concrete through the modification of nanomontorite powder and silane coupling agent.

Benefits of technology

It significantly improves the high and low temperature stability, fatigue durability and weather resistance of concrete, ensures excellent performance under extreme temperatures and heavy load conditions, and extends the service life of steel bridge deck paving.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005135273030000091
    Figure BDA0005135273030000091
  • Figure BDA0005135273030000101
    Figure BDA0005135273030000101
  • Figure BDA0005135273030000102
    Figure BDA0005135273030000102
Patent Text Reader

Abstract

The invention discloses nano-montmorillonite powder activated rubber polyurethane concrete as well as a preparation method and application thereof, and belongs to the field of building materials, the concrete is prepared from the following components in parts by weight: 100 parts of concrete aggregate, 10-20 parts of polyurethane prepolymer, 3-5 parts of activated rubber, 1-2 parts of nano-montmorillonite powder and 0.1-0.2 part of polyether polyol; adding the polyurethane prepolymer into the polyether polyol, then sequentially adding the activated rubber and the nano montmorillonite powder, and stirring at 80-95 DEG C for 3-4 hours to obtain a mixture sizing material; and adding the concrete aggregate into the mixture sizing material, and uniformly stirring. The polyurethane concrete has the characteristics of excellent high and low temperature stability, fatigue resistance durability, water resistance and corrosion resistance, high toughness, weather resistance, construction workability and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of building materials, and in particular to a nano-montmorillonite powder activated rubber polyurethane concrete and a preparation method and application thereof. Background Art

[0002] At present, asphalt is the most commonly used material for steel bridge deck paving. However, since the pavement layer is laid on the orthotropic steel bridge deck, its use environment is more stringent than that of ordinary roads. At the same time, this type of pavement is limited by the inherent characteristics of asphalt materials, resulting in unsatisfactory durability of the pavement layer and various diseases are inevitable, affecting driving safety.

[0003] In order to solve the problem of steel bridge deck paving, various new polymer binders have emerged in recent years, such as epoxy resin and polyurethane. Among them, polyurethane materials have the advantages of wide adjustable material properties, good wear resistance, good bonding performance, good elasticity, good recovery, and high mechanical strength. It is an ideal material for replacing asphalt materials and used in road paving.

[0004] CN117800649 A discloses a low-permeability, fast-curing polyurethane mixture and its preparation method, which is prepared by a single-component moisture-curing polyurethane adhesive, a limestone material combination, a compound curing agent and a compound catalyst through a certain preparation process method, which shortens the closed traffic time. However, the polyurethane concrete is prone to cracks, delamination and other diseases due to aging under the effects of ultraviolet radiation, high temperature, heavy load, etc. on the steel bridge. Based on this, a high-toughness, weather-resistant polyurethane concrete preparation method is urgently needed to solve the above technical problems. Summary of the invention

[0005] In order to solve the shortcomings of the prior art, the purpose of the present invention is to provide a nano-montmorillonite powder activated rubber polyurethane concrete and a preparation method and application thereof. The polyurethane concrete modified by nano-montmorillonite powder / activated rubber composite has better toughness, fatigue resistance, and high and low temperature tolerance, providing a more reliable and durable alternative for steel bridge deck paving.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0007] In the first aspect, the present invention provides a nano-montmorillonite powder activated rubber polyurethane concrete, which comprises, by weight, 100 parts of concrete aggregate, 10-20 parts of polyurethane prepolymer, 3-5 parts of activated rubber, 1-2 parts of nano-montmorillonite powder, and 0.1-0.2 parts of polyether polyol.

[0008] In some other embodiments, the concrete aggregate consists of coarse aggregate and fine aggregate; the weight ratio of the coarse aggregate to the fine aggregate is 1:(1-3);

[0009] Alternatively, the coarse aggregate is gravel, and the particle size of the gravel is 5-13 mm; the fine aggregate is river sand, and the particle size of the river sand is 0.075-5 mm.

[0010] In some other embodiments, the content of isocyanate groups in the polyurethane prepolymer is 10-15%, and the working viscosity is 100-600 cP at 25°C.

[0011] In some other embodiments, the activated rubber is sulfur-activated natural rubber, and the particle size of the natural rubber is 30-50 mesh;

[0012] Or, the nano-montmorillonite powder is nano-montmorillonite powder modified by a silane coupling agent; the particle size of the nano-montmorillonite powder is greater than 400 meshes;

[0013] The silane coupling agent is one or more of KH550, KH560, KH570 or A-151.

[0014] In some other embodiments, the polyether polyol is a trifunctional polyether polyol having an average molecular weight of 4000-6000.

[0015] In a second aspect, the present invention provides a method for preparing the nano-montmorillonite powder activated rubber polyurethane concrete according to the first aspect, comprising the following steps:

[0016] After adding the polyurethane prepolymer to the polyether polyol, the activated rubber and the nano-montmorillonite powder are added in sequence, and stirred at 80-95° C. for 3-4 hours to obtain a mixed rubber material;

[0017] Add concrete aggregate into the mixed rubber material, stir evenly, and obtain nano-montmorillonite powder activated rubber polyurethane concrete.

[0018] The invention first prepares a polyurethane prepolymer, then sequentially adds activated rubber, nano-montmorillonite powder and silane coupling agent, and fully mixes them. Then, the prepared mixture is mixed with coarse aggregate natural gravel and natural river sand, and then vibrated, leveled and cured. The process emphasizes the microstructure modification of the material to ensure the uniform dispersion and compatibility of the nano-material.

[0019] The addition of nano-montmorillonite powder and silane coupling agent significantly improves the high and low temperature stability of concrete, allowing it to maintain excellent performance under extreme temperatures (such as high-temperature bridge decks or low-temperature road surfaces). At the same time, it enables concrete to withstand long-term repeated stress, making it particularly suitable for bridge decks and road projects that carry heavy-loaded vehicles, ensuring that no cracks will appear during long-term use.

[0020] Through the modification of nano-montmorillonite powder and activated rubber, it is mainly used to improve the toughness, fatigue resistance, and high and low temperature tolerance of concrete.

[0021] In some other embodiments, the preparation method of the polyurethane prepolymer is: toluene diisocyanate and polyether polyol are mixed in a weight ratio of (2-4):1, and reacted at 70°C-90°C for 1-3h to obtain the prepolymer;

[0022] The polyether polyol is a trifunctional polyether polyol with an average molecular weight of 4000-6000;

[0023] Preferably, the weight ratio of toluene diisocyanate to polyether polyol is 3:1, the temperature is 80° C., and the reaction time is 2 h.

[0024] In some other embodiments, the activated rubber is prepared by mixing sulfur and natural rubber, and reacting them at 170° C.-180° C. and 0.9-1.1 MPa for 15 min-30 min;

[0025] Preferably, the weight ratio of rubber to sulfur is 100:2, the reaction temperature is 180° C., the reaction pressure is 1 MPa, and the rubber is 40-mesh natural rubber.

[0026] In some other embodiments, the modification method of the nano-montmorillonite powder is: crushing a clay ore rich in montmorillonite, adding it to a silane coupling agent solution, and reacting it at 50° C.-80° C. for 1-2 hours.

[0027] In a third aspect, the present invention provides the use of the nano-montmorillonite powder activated rubber polyurethane concrete described in the first aspect in the paving or repair of steel bridge decks.

[0028] The beneficial effects of the present invention are:

[0029] (1) The present invention utilizes polyether polyol to react with isocyanate groups in polyurethane prepolymer to form a cross-linked network, thereby improving the compactness and compressive strength of concrete. The composite modification of nano-montmorillonite powder and activated rubber improves the toughness, fatigue resistance, and high and low temperature tolerance of concrete, so that the concrete has excellent high and low temperature stability, wear resistance, weather resistance, and good construction properties, so that it can still maintain excellent performance at extreme temperatures (such as high-temperature bridge decks or low-temperature road surfaces). Since the material has good construction and workability, it can be quickly cured at room temperature, shortening the construction time, and is particularly suitable for steel bridge deck paving.

[0030] (2) The present invention effectively improves the compatibility of nano-montmorillonite powder and polyurethane by modifying the nano-montmorillonite powder with a silane coupling agent. The modified nano-montmorillonite powder has good thermal stability due to its unique layered structure; the natural rubber activated by sulfur has good dispersibility and toughness.

[0031] (3) The present invention selects nano-montmorillonite powder and activated rubber for composite modification on the basis of polyurethane modification. After the two are cross-linked, the product has certain toughness, durability, and weather resistance. After the cross-linking action of polyether polyol, the colloid and aggregate can be tightly bitten, thereby improving the performance of polyurethane concrete.

[0032] (4) The present invention improves the compactness of the structure by allowing the isocyanate group to react with the functional group that reacts with the active hydrogen atom in the polyurethane in the molecular bond design.

[0033] (5) The concrete material of the present invention has good construction and workability, does not require the addition of a curing agent, can be quickly cured at room temperature, and shortens the construction time. DETAILED DESCRIPTION

[0034] The invention provides a nano-montmorillonite powder activated rubber polyurethane concrete and a preparation method thereof. The obtained polyurethane concrete has the characteristics of excellent high and low temperature stability, fatigue resistance, waterproofness and corrosion resistance, high toughness, weather resistance, construction and workability.

[0035] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0036] The materials used in the embodiments of the present invention are all commercially available.

[0037] Example 1

[0038] The present embodiment provides a nano-montmorillonite powder activated rubber polyurethane concrete, which is prepared from the following materials, in parts by weight: 100 parts of concrete aggregate (gravel and river sand mixed in a weight ratio of 1:1, the particle size of natural gravel is 10 mm, and the particle size of natural river sand is 5 mm), 10 parts of polyurethane prepolymer, 3 parts of activated rubber, 1 part of nano-montmorillonite powder, and 0.2 parts of polyether polyol.

[0039] The specific steps of the preparation method are:

[0040] According to the above ratio, the polyurethane prepolymer was added into a magnetic stirrer with a temperature control protective cover, the temperature was set to 80°C, polyether polyol (average molecular weight of 4000) was added, and then activated rubber and nano-montmorillonite powder were added in sequence, and stirred for 4 hours to obtain a mixed rubber.

[0041] Then add coarse aggregate natural gravel and natural river sand in turn and stir for 2 minutes to fully mix the mixture rubber and aggregate, pour it into the mold, first use a scraper to preliminarily level the concrete surface, and use a vibration leveling machine to level it, which can eliminate bubbles in the concrete and ensure the compactness of the concrete. After curing at room temperature for 4 hours, remove the mold to obtain hardened nano-montmorillonite powder activated rubber polyurethane concrete.

[0042] The preparation steps of the polyurethane prepolymer are as follows: toluene diisocyanate and polyether polyol (molecular weight 4000) are mixed in a ratio of 3:1, and reacted at a temperature of 70°C for 3h to obtain a polyurethane prepolymer;

[0043] The preparation steps of the activated rubber are: selecting 40-mesh natural rubber particles and adding sulfur, with the weight ratio of rubber to sulfur being 100:2, reacting for 30 minutes under the conditions of a reaction temperature of 180° C. and a reaction pressure of 1 MPa to obtain the activated rubber;

[0044] The modification step of the nano-montmorillonite powder is as follows: the weight ratio of the nano-montmorillonite powder to the silane coupling agent KH550 is 100:2, and the mixture is stirred at 80° C. for 3 hours to obtain the nano-montmorillonite powder.

[0045] Example 2

[0046] The present embodiment provides a nano-montmorillonite powder activated rubber polyurethane concrete, which is prepared from the following materials, in parts by weight: 100 parts of polyurethane concrete aggregate (a mixture of gravel and river sand in a weight ratio of 1:2, the particle size of natural gravel is 8 mm, and the particle size of natural river sand is 3 mm), 20 parts of polyurethane prepolymer, 5 parts of activated rubber, 2 parts of nano-montmorillonite powder, and 0.1 parts of polyether polyol.

[0047] The specific steps of the preparation method are:

[0048] According to the above proportion, the polyurethane prepolymer was added into a magnetic stirrer with a temperature control protective cover, the temperature was set to 95°C, polyether polyol (average molecular weight of 5000) was added, and then activated rubber, nano-montmorillonite powder and silane coupling agent were added in sequence, and stirred for 3 hours to obtain a mixed rubber.

[0049] Then add coarse aggregate natural gravel and natural river sand in turn and stir for 2 minutes to fully mix the colloid and aggregate. Pour it into the mold. First use a scraper to preliminarily level the concrete surface and use a vibration leveling machine to level it. This can eliminate bubbles in the concrete and ensure the compactness of the concrete. After curing at room temperature for 4 hours, remove the mold to obtain hardened nano-montmorillonite powder activated rubber polyurethane concrete.

[0050] The preparation steps of the polyurethane prepolymer are as follows: toluene diisocyanate and polyether polyol (average molecular weight of 5000) are mixed in a ratio of 2:1, and reacted at a temperature of 80°C for 2h to obtain a polyurethane prepolymer;

[0051] The preparation steps of the activated rubber are: selecting 30-mesh natural rubber particles and adding sulfur, with the weight ratio of rubber to sulfur being 100:2, reacting for 30 minutes under the conditions of a reaction temperature of 170° C. and a reaction pressure of 1.1 MPa to obtain the activated rubber;

[0052] The modification preparation steps of the nano-montmorillonite powder are as follows: the weight ratio of the nano-montmorillonite powder to the silane coupling agent KH570 is 100:2, and the mixture is stirred at 90° C. for 4 hours to obtain the nano-montmorillonite powder.

[0053] Example 3

[0054] The present embodiment provides a nano-montmorillonite powder activated rubber polyurethane concrete, which is prepared from the following materials, in parts by weight: 100 parts of polyurethane concrete aggregate (a mixture of gravel and river sand in a weight ratio of 1:3, with a particle size of natural gravel of 5 mm and a particle size of natural river sand of 1 mm), 15 parts of polyurethane prepolymer, 4 parts of activated rubber, 1.5 parts of nano-montmorillonite powder, and 0.15 parts of polyether polyol.

[0055] The specific steps of the preparation method are:

[0056] According to the above proportion, the polyurethane prepolymer was added into a magnetic stirrer with a temperature control protective cover, the temperature was set to 90°C, polyether polyol (average molecular weight was 6000) was added, and then activated rubber, nano-montmorillonite powder and silane coupling agent were added in sequence, and stirred for 3 hours to obtain a mixed rubber.

[0057] Then add coarse aggregate natural gravel and natural river sand in turn and stir for 2 minutes to fully mix the colloid and aggregate. Pour it into the mold. First use a scraper to preliminarily level the concrete surface and use a vibration leveling machine to level it. This can eliminate bubbles in the concrete and ensure the compactness of the concrete. After curing at room temperature for 4 hours, remove the mold to obtain hardened nano-montmorillonite powder activated rubber polyurethane concrete.

[0058] The preparation steps of the polyurethane prepolymer are as follows: toluene diisocyanate and polyether polyol (average molecular weight of 6000) are mixed in a ratio of 4:1, and reacted at a temperature of 90°C for 1h to obtain a polyurethane prepolymer;

[0059] The preparation steps of the activated rubber are: selecting 50-mesh natural rubber particles and adding sulfur, with the weight ratio of rubber to sulfur being 100:2, reacting for 30 minutes under the conditions of a reaction temperature of 170° C. and a reaction pressure of 0.9 MPa to obtain the activated rubber;

[0060] The preparation steps of the nano-montmorillonite powder are as follows: the weight ratio of the nano-montmorillonite powder to the silane coupling agent A-151 is 100:2, and the mixture is stirred at 95° C. for 3 hours to obtain the nano-montmorillonite powder.

[0061] Comparative Example 1

[0062] The difference from Example 1 is that a one-component moisture-curing polyurethane adhesive (refer to the one-component moisture-curing polyurethane adhesive in CN 117800649A, with an NCO content of 10%-12%) is used to replace the polyurethane prepolymer in Example 1, and the other components and preparation method are exactly the same as those in Example 1.

[0063] Comparative Example 2

[0064] The difference from Example 1 is that a polyurethane prepolymer (refer to the polyurethane prepolymer in CN 102617070 A) is used to replace the polyurethane prepolymer in Example 1, and the other components and preparation method are exactly the same as those in Example 1.

[0065] Comparative Example 3

[0066] The difference from Example 1 is that modified natural rubber and natural nano-montmorillonite powder are used instead of the activated rubber and silane coupling agent nano-montmorillonite powder in Comparative Document 1, and the other ingredients and preparation method are exactly the same as those in Example 1.

[0067] Comparative Example 4

[0068] The difference from Example 1 is that no polyether polyol is added, and the other components and preparation method are exactly the same as those of Example 1.

[0069] The adhesives and concretes of the above-mentioned Examples 1-3 and Comparative Examples 1-4 were tested. The test items and test methods are shown in Tables 1 and 2.

[0070] Table 1 shows the test results of the mixed rubber

[0071]

[0072]

[0073] Table 2 Test results of concrete

[0074]

[0075] It can be seen from Table 1 and Table 2 that the nano-montmorillonite powder / activated rubber polyurethane rubber obtained in the embodiment of the present invention has good ductility, and the high and low temperature, fatigue resistance, weather resistance and other properties of the nano-montmorillonite powder / activated rubber polyurethane concrete are far better than those of the comparative example. This is because the nano-montmorillonite powder / activated rubber modifier of the present invention and the polyurethane form a relatively dense spatial network structure, which improves the high and low temperature, fatigue resistance and weather resistance of the concrete, and the nano-montmorillonite powder / activated rubber polyurethane concrete of the present invention has good construction and workability, and is characterized by convenient construction.

[0076] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A nano-montmorillonite powder activated rubber polyurethane concrete, characterized in that: The invention comprises, by weight, 100 parts of concrete aggregate, 10-20 parts of polyurethane prepolymer, 3-5 parts of activated rubber, 1-2 parts of nano-montmorillonite powder and 0.1-0.2 parts of polyether polyol.

2. The nano-montmorillonite powder activated rubber polyurethane concrete as claimed in claim 1, characterized in that: The concrete aggregate consists of coarse aggregate and fine aggregate; the weight ratio of the coarse aggregate to the fine aggregate is 1:(1-3); Alternatively, the coarse aggregate is gravel, and the particle size of the gravel is 5-13 mm; the fine aggregate is river sand, and the particle size of the river sand is 0.075-5 mm.

3. The nano-montmorillonite powder activated rubber polyurethane concrete as claimed in claim 1, characterized in that: The content of isocyanate groups in the polyurethane prepolymer is 10-15%, and the working viscosity is 100-600 cP at 25°C.

4. The nano-montmorillonite powder activated rubber polyurethane concrete as claimed in claim 1, characterized in that: The activated rubber is sulfur-activated natural rubber, and the particle size of the natural rubber is 30-50 meshes; Or, the nano-montmorillonite powder is nano-montmorillonite powder modified by a silane coupling agent; the particle size of the nano-montmorillonite powder is greater than 400 meshes; The silane coupling agent is one or more of KH550, KH560, KH570 or A-151.

5. The nano-montmorillonite powder activated rubber polyurethane concrete as claimed in claim 1, characterized in that: The polyether polyol is a trifunctional polyether polyol with an average molecular weight of 4000-6000.

6. A method for preparing the nano-montmorillonite powder activated rubber polyurethane concrete according to any one of claims 1 to 5, characterized in that: The following steps are involved: After adding the polyurethane prepolymer to the polyether polyol, the activated rubber and the nano-montmorillonite powder are added in sequence, and stirred at 80-95° C. for 3-4 hours to obtain a mixed rubber material; Add concrete aggregate into the mixed rubber material, stir evenly, and obtain nano-montmorillonite powder activated rubber polyurethane concrete.

7. The method for preparing nano-montmorillonite powder activated rubber polyurethane concrete as claimed in claim 6, characterized in that, The preparation method of the polyurethane prepolymer is as follows: toluene diisocyanate and polyether polyol are mixed in a weight ratio of (2-4):1, and reacted at 70°C-90°C for 1-3h to obtain the prepolymer; The polyether polyol is a trifunctional polyether polyol with an average molecular weight of 4000-6000; Preferably, the weight ratio of toluene diisocyanate to polyether polyol is 3:1, the temperature is 80° C., and the reaction time is 2 h.

8. The method for preparing nano-montmorillonite powder activated rubber polyurethane concrete as claimed in claim 6, characterized in that, The preparation method of the activated rubber is as follows: sulfur and natural rubber are mixed and reacted for 15 minutes to 30 minutes under the conditions of 170° C. to 180° C. and 0.9 to 1.1 MPa; Preferably, the weight ratio of rubber to sulfur is 100:2, the reaction temperature is 180° C., the reaction pressure is 1 MPa, and the rubber is 40-mesh natural rubber.

9. The method for preparing nano-montmorillonite powder activated rubber polyurethane concrete as claimed in claim 6, characterized in that: The modification method of the nano-montmorillonite powder is as follows: crushing clay ore rich in montmorillonite, adding it into a silane coupling agent solution, and reacting it at 50° C.-80° C. for 1-2 hours.

10. Use of the nano-montmorillonite powder activated rubber polyurethane concrete according to any one of claims 1 to 5 in steel bridge deck paving or repairing.

Citation Information

Patent Citations

  • Polyurethane asphalt concrete as well as preparation method and application thereof

    CN102617070A

  • Low-water-seepage fast-curing polyurethane mixture and preparation method thereof

    CN117800649A